2000
DOI: 10.1007/s005920070013
|View full text |Cite
|
Sign up to set email alerts
|

Chronic effects of streptozotocin-induced diabetes on the ultrastructure of rat ventricular and papillary muscle

Abstract: Contractile dysfunctions have been demonstrated in different experimental models of diabetes which have similar characteristics to many of the abnormalities found in the clinical setting. Administration of streptozotocin (STZ) to young adult rats induces beta-cell necrosis of the pancreas which gives rise to hypoinsulinaemia and hyperglycaemia, features which are also seen in untreated type 1 clinical diabetes. We have investigated the chronic effects of STZ-induced diabetes on contraction in rat ventricular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 0 publications
5
7
0
2
Order By: Relevance
“…Resting cell length was similar in EPI and ENDO myocytes from STZ-treated rats and controls. These results are consistent with previous studies that have variously demonstrated unchanged resting cell length, width, and the calculated cell volume in myocytes isolated from whole ventricle from STZ-treated rats compared to controls (Howarth et al 2000(Howarth et al , 2002Hamouda et al 2015). However, differences have been reported in other regional cell measurements.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Resting cell length was similar in EPI and ENDO myocytes from STZ-treated rats and controls. These results are consistent with previous studies that have variously demonstrated unchanged resting cell length, width, and the calculated cell volume in myocytes isolated from whole ventricle from STZ-treated rats compared to controls (Howarth et al 2000(Howarth et al , 2002Hamouda et al 2015). However, differences have been reported in other regional cell measurements.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with previous studies that have variously demonstrated unchanged resting cell length, width, and the calculated cell volume in myocytes isolated from whole ventricle from STZ‐treated rats compared to controls (Howarth et al. , ; Hamouda et al. ).…”
Section: Discussionsupporting
confidence: 92%
“…In fact, the cardiac content of noradrenaline and noradrenaline turnover, uptake, synthesis and release have been demonstrated to all be enhanced in diabetic cardiomyopathy (Ganguly etal 1987), which might lead to down-regulation of cardiac b-adrenoceptors, resulting in a deficiency in b 1adrenoceptor-mediated stimulation. As reported previously, we also found that diabetes results in an increased responsiveness of papillary muscle to noradrenaline and isoprenaline (Austin & Chess-Williams 1992;Howarth et al 2000). The mechanisms of contrary responsiveness of diabetic atria and papillary muscle to b-adrenoceptor agonists are not known, but similar controversial findings were reported previously (Dinçer et al 1998).…”
Section: Morphology Of Ventricular Tissuesupporting
confidence: 90%
“…These findings are consistent with previous reports that also showed loss of myofibrils in the diabetic cardiomyocytes. In addition, the researchers pointed out that there were no changes in sarcomere length related to DM [25]. However, the sarcomere length was not measured in the present study.…”
Section: Discussionmentioning
confidence: 53%